Proceedings of the 41st Annual Hawaii International Conference on System Sciences (HICSS 2008) 2008
DOI: 10.1109/hicss.2008.476
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Development and Usage of Social Networking Sites: The Social Software Performance Model

Abstract: Social networking sites such as MySpace and Facebook thrive on energetic social interaction, but the factors that assure this are not well understood. There is a lack of theory that can describe and predict the successful adoption of new social computing systems. This paper introduces the Social Software Performance Model, and uses it to interpret the evolution and usage of social networking sites. Drawing from socio-technical systems theory, task technology fit, and structuration theory, this model identifies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 27 publications
0
21
0
1
Order By: Relevance
“…While developed in the 1990s to explain patterns of use in group support systems (GSS), AST has recently been applied to analyses of social software [13,14,18,28]. While this paper specifically focuses on measures of appropriation, a more detailed description of AST and its application to the study of SNS can be found in [14,18].…”
Section: The Importance Of Reliable Measures For Social Computingmentioning
confidence: 99%
See 1 more Smart Citation
“…While developed in the 1990s to explain patterns of use in group support systems (GSS), AST has recently been applied to analyses of social software [13,14,18,28]. While this paper specifically focuses on measures of appropriation, a more detailed description of AST and its application to the study of SNS can be found in [14,18].…”
Section: The Importance Of Reliable Measures For Social Computingmentioning
confidence: 99%
“…Few if any measures for items regarding the use of these sites were available, and so these had to be developed and validated. More detailed descriptions of prior studies can be found in [15][16][17][18].…”
Section: Empirical Tests Of Privacy Management Scalesmentioning
confidence: 99%
“…A definition provided by boyd and Ellison (boyd & Ellison, 2008) outlines three main features that define SNSs and will be used for the purposes of this research. SNSs are "web-based services that allow individuals to (1) construct a public or semi-public profile within a bounded system, (2) articulate a list of other users with whom they share a connection, and (3) (Dwyer, Hiltz, & Widmeyer, 2008).…”
Section: Defining Snss and Its Usementioning
confidence: 99%
“…Academic research related to SNS focuses on many different facets, including (but not limited to) user behavior (e.g., Bolar, 2009;Ellison, Steinfield, & Lampe, 2007), privacy and trust (e.g., Acquisti & Gross, 2006;Dwyer, Hiltz, & Widmeyer, 2008) and the unique properties of social networks (e.g., Boyd & Ellison, 2008;Richter & Koch, 2008). Recently, studies that are devoted to modeling the textual content generated by SNS users have emerged.…”
Section: Overviewmentioning
confidence: 99%